2015
DOI: 10.1186/s12977-015-0174-4
|View full text |Cite
|
Sign up to set email alerts
|

SAMHD1 specifically restricts retroviruses through its RNase activity

Abstract: BackgroundHuman SAMHD1 possesses dual enzymatic functions. It acts as both a dGTP-dependent triphosphohydrolase and as an exoribonuclease. The dNTPase function depletes the cellular dNTP pool, which is required for retroviral reverse transcription in differentiated myeloid cells and resting CD4+ T cells; thus this activity mainly plays a role in SAMHD1-mediated retroviral restriction. However, a recent study demonstrated that SAMHD1 directly targets HIV-1 genomic RNA via its RNase activity, and that this funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 42 publications
5
61
1
Order By: Relevance
“…This finding raised the possibility that SAMHD1 does not restrict HIV-1 solely by dNTP pool depletion. Previous reports suggested that SAMHD1 has ribonuclease that degrades the viral genomic RNA in an infected cell (6,24). Our findings do not support this possibility.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding raised the possibility that SAMHD1 does not restrict HIV-1 solely by dNTP pool depletion. Previous reports suggested that SAMHD1 has ribonuclease that degrades the viral genomic RNA in an infected cell (6,24). Our findings do not support this possibility.…”
Section: Discussioncontrasting
confidence: 99%
“…The phosphohydrolase and RNase activities have been genetically separated such that mutation at D137A causes the loss of phosphohydrolase activity, whereas mutation at Q548A causes the loss of the RNase activity. Analysis of these mutated enzymes suggested that that restriction requires only the RNase activity (6,24). These issues remain to be resolved, as the nuclease activities have been questioned in subsequent reports (25,26).…”
Section: The Lentiviral Restriction Factor Samhd1mentioning
confidence: 99%
See 1 more Smart Citation
“…6), raising the question for its mode of action. Our data support a model in which the positive effects of VprBP for cellular and viral gene expression in infected cells are at least partially exerted via degradation of its binding partner SAMHD1, which is known to deplete cellular dNTP levels and to degrade viral RNA (56,58,77). Indeed, we detected decreased SAMHD1 expression levels during permissive Pan infection (Fig.…”
Section: Functional Validation Of Significant Protein Signatures Bysupporting
confidence: 88%
“…SAMHD1 potentially can block HIV replication through two distinct enzymatic functions. SAMHD1 can degrade viral nucleic acids through its exonuclease activity (19,20) and deplete the intracellular deoxynucleoside triphosphate (dNTP) pool through its dNTP triphosphatase activity (17). The relative contribution of each activity to the inhibition of HIV replication is the subject of intense debate (21,22).…”
mentioning
confidence: 99%